Perfluorosulfonic acid proton exchange composite membrane

By impregnating and drying porous base membranes with a mixed solvent system combining good and bad solvents, the problem of insufficient pore filling under a single solvent system was solved, and a perfluorosulfonic acid proton exchange composite membrane with high mechanical strength and high proton conductivity was achieved, thus improving the performance of fuel cells.

CN121181995AInactive Publication Date: 2025-12-23JILIN ZHONGDING ELECTRIC POWER TECH DEV CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511386272.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2025-12-23
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing technology, a single solvent system is difficult to achieve sufficient and dense pore filling of hydrophobic base films, resulting in a decrease in proton conduction efficiency and easy generation of interface defects.

Method used

A perfluorosulfonic acid proton exchange composite membrane was prepared by impregnating and filling a porous base membrane with a mixed solvent system of good solvent and poor solvent in a volume ratio of 100:0 to 40:60, followed by drying and protonation treatment.

Benefits of technology

The prepared perfluorosulfonic acid proton exchange composite membrane has both excellent mechanical strength and dimensional stability, ensuring high proton conductivity and improving the durability and reliability of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005615306980000091
    Figure BDA0005615306980000091
  • Figure BDA0005615306980000101
    Figure BDA0005615306980000101
Patent Text Reader

Abstract

The invention is applicable to the technical field of proton exchange membranes, and particularly relates to a perfluorosulfonic acid proton exchange composite membrane which is prepared by the following steps: preparing a perfluorosulfonic acid resin solution: dissolving the perfluorosulfonic acid resin solution in a mixed solvent to form a membrane casting solution; impregnating and filling: impregnating a porous base membrane in the obtained perfluorinated sulfonic acid resin solution, and keeping at 20-80 DEG C for 1-120 minutes; drying and forming: taking out the impregnated film, and drying to form a composite film; and protonation treatment: treating the composite membrane in an acid solution, and washing to be neutral to obtain the perfluorosulfonic acid proton exchange composite membrane. According to the invention, the problems of deformation and damage of the battery in operation are effectively avoided; meanwhile, the high proton conductivity is ensured, so that the ion transmission efficiency is maintained; the introduction of the ePTFE porous skeleton enhances the membrane body and reduces the use amount of the perfluorinated sulfonic acid resin at the same time, the composite membrane is compact in structure and balanced in performance, and the durability and reliability of the fuel cell are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of proton exchange membrane technology, and particularly relates to a perfluorosulfonic acid proton exchange composite membrane. Background Technology

[0002] Composite proton exchange membranes are novel electrolyte membranes created by combining a polymer matrix with inorganic materials (such as metal oxide clusters, graphene oxide, metal-organic frameworks (MOFs)) or functional nanomaterials. Their core design principle lies in enhancing proton conductivity, mechanical strength, thermal stability, and gas barrier properties through the synergistic effect of multiple components, while simultaneously reducing material costs. For example, combining perfluorosulfonic acid membranes with high specific surface area inorganic fillers (such as MOFs) can form dense proton transport channels, while the combination of polymer brushes and ultraacidic metal clusters can achieve structural stability and efficient proton conduction at high temperatures.

[0003] Existing composite membrane preparation methods suffer from the problem that a single solvent system cannot fully and densely fill the pores of hydrophobic base membranes, easily generating interface defects, which leads to a decrease in proton conduction efficiency. Summary of the Invention

[0004] The purpose of this invention is to provide a perfluorosulfonic acid proton exchange composite membrane, which aims to solve the problem that a single solvent system is difficult to achieve sufficient and dense pore filling of hydrophobic base membranes, easily generating interface defects, thereby leading to a decrease in proton conduction efficiency.

[0005] This invention is achieved by providing a perfluorosulfonic acid proton exchange composite membrane, the preparation steps of which are as follows:

[0006] (1) Preparation of perfluorosulfonic acid resin solution: Dissolve perfluorosulfonic acid resin in a mixed solvent to form a casting solution with a solid content of 1wt% to 20wt%; the mixed solvent is prepared by compounding a good solvent and a bad solvent in a volume ratio of 100:0 to 40:60.

[0007] (2) Impregnation and filling: The porous base membrane is impregnated in the perfluorosulfonic acid resin solution obtained in step (1) and kept at 20°C to 80°C for 1 minute to 120 minutes to allow the perfluorosulfonic acid resin to fully fill the pores of the porous base membrane.

[0008] (3) Drying and shaping: Take out the impregnated membrane and dry it at 50°C to 150°C for 5 to 120 minutes to evaporate and remove the mixed solvent, thus forming a composite membrane;

[0009] (4) Protonation treatment: The dried composite membrane is placed in an acid solution for treatment, and then washed with deionized water until neutral to obtain the perfluorosulfonic acid proton exchange composite membrane.

[0010] Preferably, in the mixed solvent, the good solvent is one or more of water, ethanol, isopropanol, n-propanol, methanol, and ethylene glycol; and the bad solvent is one or more of 1-butanol, 2-butanol, n-pentanol, n-hexane, and n-heptane.

[0011] Preferably, the solid content of the casting solution is 5 wt% to 15 wt%.

[0012] Preferably, the porous base membrane is an expanded polytetrafluoroethylene porous membrane, a polyethylene porous membrane, a polypropylene porous membrane, or a polyimide porous nanofiber membrane.

[0013] Preferably, the thickness of the expanded polytetrafluoroethylene porous membrane is 5 μm to 50 μm, and the porosity is 50% to 95%.

[0014] Preferably, the immersion temperature in step (2) is 40°C to 60°C, and the holding time is 30 minutes to 60 minutes.

[0015] Preferably, in step (2), the porous base membrane is subjected to plasma treatment or ultraviolet ozone treatment before impregnation.

[0016] Preferably, the drying in step (3) is carried out in two stages: first, drying at 60°C to 80°C for 20 to 40 minutes, and then heat-treating at 120°C to 140°C for 10 to 30 minutes.

[0017] Preferably, the protonation treatment is performed at a temperature of 60°C to 90°C for a duration of 30 to 120 minutes.

[0018] Preferably, after step (4), the process further includes annealing the obtained perfluorosulfonic acid proton exchange composite membrane under vacuum conditions at 80°C to 120°C for 1 to 4 hours.

[0019] The perfluorosulfonic acid proton exchange composite membrane provided by this invention uses a mixed system of good and bad solvents to impregnate and fill a porous base membrane. The prepared perfluorosulfonic acid proton exchange composite membrane has both excellent mechanical strength and dimensional stability, effectively avoiding deformation and damage problems during battery operation; at the same time, it ensures high proton conductivity, so that ion transport efficiency can be maintained; the introduction of ePTFE porous framework strengthens the membrane while reducing the amount of perfluorosulfonic acid resin used. The composite membrane has a dense structure and balanced performance, which greatly improves the durability and reliability of fuel cells. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0021] A perfluorosulfonic acid proton exchange composite membrane, characterized in that the preparation steps of the perfluorosulfonic acid proton exchange composite membrane are as follows:

[0022] (1) Preparation of perfluorosulfonic acid resin solution: Perfluorosulfonic acid resin is dissolved in a mixed solvent to form a casting solution with a solid content of 1 wt% to 20 wt%; the mixed solvent is prepared by compounding a good solvent and a poor solvent in a volume ratio of 100:0 to 40:60. The good solvent is one or more of water, ethanol, isopropanol, n-propanol, methanol, and ethylene glycol; the poor solvent is one or more of 1-butanol, 2-butanol, n-pentanol, n-hexane, and n-heptane, and the solid content of the casting solution is 5 wt% to 15 wt%.

[0023] In this step, the selected perfluorosulfonic acid resin is an ionomer with a unique microstructure. Its main chain is a hydrophobic polytetrafluoroethylene structure, while the side chains have hydrophilic sulfonic acid groups (-SO3H) at their ends. These sulfonic acid groups possess strong chemical stability and proton conductivity, requiring specific conditions for dissolution. In the mixed solvent system, the main role of the good solvent (such as lower alcohols, water, etc.) is to disrupt the interactions between resin molecular chains, promoting resin swelling and eventual dissolution to form a transparent solution. Its function is to provide the necessary dissolving power. The poor solvent is used to moderately reduce the overall solvent system's dissolving capacity for the resin, controlling the degree of resin molecular chain expansion and solution viscosity. Furthermore, in the subsequent drying process, the poor solvent typically has a higher boiling point and a slower evaporation rate, which allows the resin molecular chains more time to arrange themselves in an orderly manner and precipitate slowly. This avoids defects such as skin formation on the film surface, internal voids, or cracks caused by excessively rapid solvent evaporation, ultimately resulting in a denser and more uniform filled structure. The solid content should be controlled within the range of 1wt% to 20wt%. If the solid content is too low, the solution viscosity will be low. Although it is easy to penetrate, the resin loading will be insufficient, resulting in a low conductivity of the final composite membrane. If the solid content is too high, the solution viscosity will be too high, the fluidity will be poor, and it will be difficult to fully penetrate into the deep pores of the complex three-dimensional network of the porous base membrane, which will easily lead to incomplete filling.

[0024] (2) Impregnation and Filling: The porous base membrane is impregnated in the perfluorosulfonic acid resin solution obtained in step (1) and kept at 20°C to 80°C for 1 minute to 120 minutes to allow the perfluorosulfonic acid resin to fully fill the pores of the porous base membrane. The porous base membrane is an expanded polytetrafluoroethylene porous membrane, a polyethylene porous membrane, a polypropylene porous membrane, or a polyimide porous nanofiber membrane. The thickness of the expanded polytetrafluoroethylene porous membrane is 5 μm to 50 μm, and the porosity is 50% to 95%. The impregnation temperature is 40°C to 60°C, and the holding time is 30 minutes to 60 minutes.

[0025] In this step, the resin solution prepared in step (1) is completely and uniformly embedded into every pore of the porous matrix. The selected porous base membrane (such as expanded polytetrafluoroethylene ePTFE membrane) itself is the main bearer of mechanical strength, and its interior has an interconnected, high-porosity nano / micro fiber network structure. The base membrane is immersed in the resin solution, and through capillary force and possible external driving force (such as slight negative pressure), the solution spontaneously permeates and occupies the pore space. Setting the immersion temperature between 20℃ and 80℃ is a key process parameter. Increasing the temperature can effectively reduce the viscosity of the resin solution, enhance its fluidity and permeability, and enable it to enter finer pores more quickly; at the same time, heat energy can increase the mobility of polymer chain segments, which is beneficial to the spreading and adsorption of resin on the surface and inside of the base membrane. However, the higher the temperature, the better. Excessively high temperatures may cause the solvent to evaporate too quickly or generate convection on the liquid surface, which may affect the uniformity of filling. The immersion time (1 minute to 120 minutes) ensures that the permeation process is fully completed. If the time is too short, the penetration will be incomplete, leaving unfilled voids inside the base membrane, which will become a performance bottleneck. If the time is too long, it will reduce production efficiency and may affect the structural stability of the base membrane due to the long-term swelling effect of the solvent. The ultimate goal of this step is to ensure that the perfluorosulfonic acid resin solution fully fills all pores, laying a solid structural foundation for the next step of forming continuous, defect-free proton conduction channels.

[0026] (3) Drying and shaping: Take out the impregnated film and dry it at 50°C to 150°C for 5 to 120 minutes to evaporate and remove the mixed solvent, forming a composite film. The drying is carried out in two stages: first, dry at 60°C to 80°C for 20 to 40 minutes, and then heat treat at 120°C to 140°C for 10 to 30 minutes.

[0027] In this step, while removing the solvent, the resin is transformed from a solution state into a solid film firmly attached to the base membrane framework, thus permanently fixing the temporary "impregnation" structure into the final "composite membrane" structure. After removing the saturated membrane from the solution, controlling the drying temperature (50°C to 150°C) and time (5 minutes to 120 minutes) is crucial. The drying process must follow the principle of "low temperature first, then high temperature." In the initial low-temperature stage (e.g., 50°C-80°C), the aim is to allow most of the good solvent and some of the poor solvent to evaporate at a gradual rate. If the initial temperature is too high, rapid solvent bubbling will cause a dense skin layer to quickly form on the membrane surface. This skin layer will hinder the subsequent escape of the internal solvent, and the vapor pressure generated internally may expand the already formed structure, ultimately forming honeycomb-like macroscopic defects or microcracks within the membrane, severely damaging the membrane's integrity and mechanical properties. After most of the solvent has evaporated, the process enters a higher temperature stage (e.g., 120℃-150℃). One purpose of this stage is to thoroughly remove residual, high-boiling-point undesirable solvents and bound water. The second purpose is to perform a brief heat treatment (annealing) on ​​the perfluorosulfonic acid resin, which promotes the movement of resin molecular chain segments, causing further relaxation and rearrangement, eliminating internal stress, and enhancing the interfacial bonding force between the resin itself and the base film, thereby improving the density, stability, and mechanical strength of the composite film.

[0028] (4) Protonation treatment: The dried composite membrane is placed in an acid solution for treatment, and then washed with deionized water until neutral to obtain the perfluorosulfonic acid proton exchange composite membrane. The acid solution is a sulfuric acid, hydrochloric acid, or nitric acid solution with a concentration of 0.5 mol / L to 3.0 mol / L; the protonation treatment temperature is 60°C to 90°C, and the treatment time is 30 minutes to 120 minutes.

[0029] In this step, after drying, the sulfonic acid groups in the perfluorosulfonic acid resin of the composite membrane typically exist in the form of inert alkali metal cations (such as Na+ type, -SO3Na), and this type of membrane hardly conducts protons. The purpose of the protonation treatment is to convert all these -SO3Na groups into proton-exchangeable hydrogen ions (-SO3H). The dried composite membrane is then immersed in an acid solution of a certain concentration and temperature (usually dilute sulfuric acid, hydrochloric acid, or nitric acid), and the H+ in the solution... + It will react with Na on the resin + An ion exchange reaction occurs (-SO3Na+H) + →-SO3H+Na +To improve exchange efficiency and thoroughness, a certain processing temperature (typically heated to 60-90℃) and sufficient processing time need to be maintained. After the reaction, a large amount of acid and exchanged metal salt ions remain inside and on the surface of the membrane. Therefore, it is necessary to repeatedly wash with large amounts of deionized water until the pH of the washing solution is neutral to ensure that all impurity ions are completely removed. Any residual impurity ions can poison the catalyst or generate additional resistance during fuel cell operation, severely reducing battery performance and lifespan.

[0030] The effectiveness of this invention is demonstrated through the following controlled experiments:

[0031] Performance testing methods:

[0032] Proton conductivity (σ): Measured using the four-electrode AC impedance method. The membrane strip (1cm × 4cm) was placed in a constant temperature and humidity chamber at 80℃ and 100% RH for 2 hours to equilibrate, and then its impedance was measured. The conductivity was calculated using the formula σ = L / (R × W × T), where L is the distance between the two reference electrodes, R is the impedance, and W and T are the width and thickness of the membrane, respectively.

[0033] Swelling Ratio: The membrane was cut into 5cm × 5cm squares and dried in a vacuum drying oven at 50℃ for 24 hours. Its area (A_dry) was then accurately measured. Subsequently, it was completely immersed in deionized water at 80℃ for 2 hours. After removal, the surface moisture was gently blotted with filter paper, and its wet area (A_wet) was immediately measured. Swelling ratio = [(A_wet - A_dry) / A_dry] × 100%.

[0034] Tensile Strength: Tested according to ASTM D882 standard. Cut the membrane into dumbbell-shaped strips (50 mm long, 4 mm wide at the narrowest point) and test them on a universal testing machine at a tensile rate of 10 mm / min until the membrane breaks. Take the average of at least 5 samples.

[0035] Film thickness: Measure at least 5 times at different locations on the film using a micrometer and take the average value.

[0036] Comparative Example 1 (D1): Preparation of homogeneous PFSA membranes by conventional solution casting method

[0037] Solution preparation: Weigh 5.0 g of perfluorosulfonic acid resin (PFSA) and add it to a capped glass bottle containing 45.0 g of mixed solvent (ethanol and deionized water, volume ratio 7:3).

[0038] Dissolution: Place the glass bottle in an 80°C water bath and mechanically stir at 200 rpm for 6 hours until the resin is completely dissolved, resulting in a clear and transparent casting solution with a solid content of 10 wt%.

[0039] Degassing by standing: Let the obtained casting solution stand at room temperature for 12 hours to remove air bubbles.

[0040] Casting film formation: Pour an appropriate amount of casting solution onto a horizontal, clean glass plate, and use a doctor blade to control the gap between the castings to be 500 μm, and cast the film at a uniform speed.

[0041] Drying: Transfer the glass plate with the wet film to an 80°C forced-air drying oven and dry for 2 hours.

[0042] Peel off the film: Carefully peel off the dry, transparent film from the glass plate.

[0043] Acid treatment and washing: The removed membrane was immersed in a 1.0 mol / L sulfuric acid solution and treated at 80°C for 1 hour. Subsequently, the membrane was repeatedly washed several times with a large amount of deionized water at 80°C, soaking for 30 minutes each time, until the pH of the washing water was neutral.

[0044] Storage: Immerse the final homogenized membrane in deionized water for later use.

[0045] Comparative Example 2 (D2): ePTFE membrane impregnated with a single solvent (ethanol / water)

[0046] Solution preparation: Weigh 5.0 g of perfluorosulfonic acid resin (PFSA) and add it to a capped glass bottle containing 45.0 g of mixed solvent (ethanol and deionized water, volume ratio 7:3).

[0047] Dissolution: Place the glass bottle in a water bath at 80°C and mechanically stir at 200 rpm for 6 hours to obtain a casting solution with a solid content of 10 wt%.

[0048] Impregnation: Take a 10cm×10cm ePTFE base membrane and completely immerse it in the above casting solution. Keep the system in a constant temperature water bath at 60℃ and let it soak for 60 minutes.

[0049] Remove: Use tweezers to remove the soaked membrane from the solution and let it drip off naturally to remove excess solution from the surface.

[0050] Drying: Fix the membrane onto the frame and place it in an 80°C forced-air drying oven for 2 hours.

[0051] Acid treatment and washing: The dried composite membrane was immersed in a 1.0 mol / L sulfuric acid solution and treated at 80°C for 1 hour. Subsequently, the membrane was repeatedly washed several times with a large amount of deionized water at 80°C until the wash water was neutral.

[0052] Storage: Immerse the final composite membrane in deionized water for later use.

[0053] Example 1 (E1): The method of the present invention (ethanol / 1-butanol mixed solvent)

[0054] Solution preparation: Weigh 5.0 g of perfluorosulfonic acid resin (PFSA) and add it to a capped glass bottle containing 45.0 g of mixed solvent (ethanol and 1-butanol, volume ratio 6:4).

[0055] Dissolution: Place the glass bottle in an 80°C water bath and mechanically stir at 200 rpm for 8 hours to obtain a homogeneous, semi-transparent casting solution.

[0056] Impregnation: Take a 10cm×10cm ePTFE base membrane and completely immerse it in the above casting solution. Keep the system in a constant temperature water bath at 60℃ and let it soak for 60 minutes.

[0057] Removal and Pre-drying: Use tweezers to remove the impregnated film and let it hang to drain for 10 seconds. Then lay it flat on a PTFE plate and place it in an 80°C forced-air drying oven for 30 minutes.

[0058] Heat treatment: The temperature is then raised to 130°C and heat treatment is continued for 20 minutes.

[0059] Acid treatment and washing: Immerse the cooled membrane in a 1.0 mol / L sulfuric acid solution and treat at 80°C for 1 hour. Then wash the membrane repeatedly with plenty of 80°C deionized water until the wash water is neutral.

[0060] Storage: Immerse the final composite membrane in deionized water for later use.

[0061] Example 2 (E2): The method of the present invention (isopropanol / 1-butanol mixed solvent)

[0062] Solution preparation: Weigh 6.67 g of perfluorosulfonic acid resin (PFSA) and add it to a capped glass bottle containing 43.33 g of mixed solvent (isopropanol and 1-butanol, volume ratio 1:1).

[0063] Dissolution: Place the glass bottle in a water bath at 85°C and mechanically stir at 250 rpm for 10 hours to obtain a homogeneous casting solution (solid content of 13.3 wt%).

[0064] Base film pretreatment: Place the ePTFE base film in a UV ozone cleaner for 15 minutes.

[0065] Immersion: Immerse the pretreated base film in the casting solution and keep it at 50°C for 90 minutes.

[0066] Removal and Drying: After removing the membrane, a two-stage drying process is adopted: 70℃ / 40 minutes + 120℃ / 30 minutes.

[0067] Acid treatment and washing: Treat with 1.5 mol / L sulfuric acid solution at 85°C for 90 minutes. Then wash with deionized water until neutral.

[0068] Storage: Immerse the final composite membrane in deionized water for later use.

[0069]

[0070]

[0071] Note: This indicates that the value is the best or second best value in its class, significantly better than all comparable values.

[0072] Test environment: Proton conductivity was measured at 80℃ and 100% relative humidity; swelling rate was measured in deionized water at 80℃.

[0073] The data is expressed as: mean ± standard deviation.

[0074] The results above show that the composite membranes prepared by the present invention (E1, E2) have a tensile strength (~45-48 MPa) that is more than 2.5 times that of the homogeneous membrane (D1) in Comparative Example 1, while the area swelling ratio (~12%) is less than half that of the homogeneous membrane (D1), exhibiting unparalleled mechanical properties and dimensional stability. Despite the introduction of a non-conductive ePTFE reinforcing framework, through an optimized mixed solvent impregnation process, the electrical conductivity of the membrane of the present invention (>0.120 S / cm) is much higher than that of the incompletely filled D2, and maintains the same high level as the high-performance homogeneous membrane D1, successfully resolving the contradiction between strength and conductivity. The performance shortcomings of Comparative Example D2 demonstrate the inherent defects of a single solvent system in impregnation and filling, while the good / bad solvent blending system used in the present invention achieves sufficient and dense pore filling, resulting in superior overall performance.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A perfluorosulfonic acid proton exchange composite membrane, characterized in that, The preparation steps of the perfluorosulfonic acid proton exchange composite membrane are as follows: (1) Preparation of perfluorosulfonic acid resin solution: Dissolve perfluorosulfonic acid resin in a mixed solvent to form a casting solution with a solid content of 1wt% to 20wt%; the mixed solvent is prepared by compounding a good solvent and a bad solvent in a volume ratio of 100:0 to 40:

60. (2) Impregnation and filling: The porous base membrane is impregnated in the perfluorosulfonic acid resin solution obtained in step (1) and kept at 20°C to 80°C for 1 minute to 120 minutes to allow the perfluorosulfonic acid resin to fully fill the pores of the porous base membrane. (3) Drying and shaping: Take out the impregnated membrane and dry it at 50°C to 150°C for 5 to 120 minutes to evaporate and remove the mixed solvent, thus forming a composite membrane; (4) Protonation treatment: The dried composite membrane is placed in an acid solution for treatment, and then washed with deionized water until neutral to obtain the perfluorosulfonic acid proton exchange composite membrane.

2. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, In the mixed solvent, the good solvent is one or more of water, ethanol, isopropanol, n-propanol, methanol, and ethylene glycol; the bad solvent is one or more of 1-butanol, 2-butanol, n-pentanol, n-hexane, and n-heptane.

3. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, The solid content of the casting solution is 5 wt% to 15 wt%.

4. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, The porous base membrane is an expanded polytetrafluoroethylene porous membrane, a polyethylene porous membrane, a polypropylene porous membrane, or a polyimide porous nanofiber membrane.

5. The perfluorosulfonic acid proton exchange composite membrane according to claim 4, characterized in that, The thickness of the expanded polytetrafluoroethylene porous membrane is 5 μm to 50 μm, and the porosity is 50% to 95%.

6. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, The immersion temperature in step (2) is 40°C to 60°C, and the holding time is 30 minutes to 60 minutes.

7. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, In step (2), the porous base membrane is subjected to plasma treatment or ultraviolet ozone treatment before impregnation.

8. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, The drying process in step (3) is carried out in two stages: first, drying at 60°C to 80°C for 20 to 40 minutes, and then heat-treating at 120°C to 140°C for 10 to 30 minutes.

9. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, The acid solution mentioned in step (4) is a sulfuric acid, hydrochloric acid or nitric acid solution with a concentration of 0.5 mol / L to 3.0 mol / L; the temperature of the protonation treatment is 60°C to 90°C and the treatment time is 30 minutes to 120 minutes.

10. The perfluorosulfonic acid proton exchange composite membrane according to claim 1, characterized in that, The process after step (4) further includes annealing the obtained perfluorosulfonic acid proton exchange composite membrane under vacuum conditions at 80°C to 120°C for 1 to 4 hours.

Citation Information

Cited By

  • High-antioxidant perfluorosulfonic acid composite cation exchange membrane as well as preparation method and application thereof

    CN122098275A

  • High-oxidation-resistance perfluorosulfonic acid composite cation exchange membrane, preparation method and application thereof

    CN122098275B